DETERMINATION OF JURISDICTIONS IN DISPUTES ABOUT PROTECTION OF OWNERSHIP - Сопілко, Ірина Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Objective: to explore scientific and practical guidance on the division of jurisdictions in property rights disputes. Research methods: logical, formal-dogmatic, comparative-legal, etc. Results: it is stated that the formulated approaches to the understanding of judicial jurisdiction make it difficult to protect the infringed law for specific entities requiring such protection, which indicates the need to distinguish categories of disputes, which are considered in administrative proceedings from those that considered in civil proceedings. Discussion: problems of legal regulation of property relations in Ukraine, analysis of the shortcomings of legal regulation of protection of property rights, proposals to improve the mechanism of protection of property rights. In order to implement economic, legal and political reforms, it is necessary to improve the system of property rights protection as a basic indicator of investor confidence in the state, including to promote the quality of administrative legislation and to develop theoretical proposals for improving its practice in the field of property rights protection in Ukraine. Different approaches to the understanding of judicial jurisdiction make it difficult to protect the infringed right for specific entities that need such protection. Referring to case law, the most contentious situations regarding the jurisdiction of disputes are the category of disputes concerning the protection of property rights, in particular, involving the authorities. At present, there are divergent views on the jurisdiction of such disputes. Therefore, we believe that the criteria for determining the jurisdiction of disputes must be clearly set out in order to protect the infringed property right by involving the courts and scholars in the fields of civil, administrative law and related fields of law. In conducting such research, it is important to properly identify the nature of the dispute, a reasoned request to an administrative court or other court to protect the rights, freedoms, interests, and protection of the owner’s rights in property relations disputes and a clear mechanism for the protection of the infringed right.